The Resilient Organisation: A Meta‐Analysis of the Effect of Communication on Team Diversity and Team Performance. Issue 4 (11th June 2019) - Bui, Hong; Chau, Vinh Sum; Degl'Innocenti, Marta; Leone, Ludovica; Vicentini, Francesca
Abstract : The Input‐Process‐Output framework is adopted to examine the impact of diversity attributes (the input) on communication (the process) and their influence on performance (the output), to understand the internal group/team working mechanisms of organisational resilience. A meta‐analysis of 174 correlations from 35 empirical studies undertaken over 35 years (1982–2017) showed that members of a team who have different experiences are more likely to share information and communicate openly when they deal with a task that requires collaboration outside the team. This supports the view that organisations are more resilient by being more closely connected with the external environment. Differences in social categories tend to favour openness of communication, especially in the case of age diversity and race/ethnicity diversity. An increase in openness of communication is likely to enhance team performance, particularly for small and medium‐sized teams operating in manufacturing industries, while frequency of communication can be beneficial for both large and medium‐sized teams working in the high technology industry. The positive workings of these associations form the resilient organisation.